1966
DOI: 10.1029/jz071i014p03523
|View full text |Cite
|
Sign up to set email alerts
|

Electrical transients observed during underground nuclear explosions

Abstract: Electrical transients were recorded from eleven underground nuclear explosions at the Nevada Test Site and from one near Carlsbad, New Mexico. The electric field components are only a few microvolts per meter at distances less than 10 km from the shot point, and they generally decay approximately as the inverse cube of distance. Magnitudes are proportional to about the 0.4 power of yield. Two source mechanisms are considered: the formation of an elementary magnetic dipole by the conductive plasma expanding in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Thermohydraulic explosion represents the most violent phreatomagmatic activity, that is, the phreatomagmatic explosion [Zimanowski, 1998]. In the context of fragmentation of solid material [e.g., Petrenko and Gluschenkov, 1996;Yoshida et al, 1997Yoshida et al, , 1998], impact events [e.g., Crawford and Schultz, 1988; Adushkin and Soloviev, 2819 1996], and nuclear explosion [e.g., Zablocki, 1966], very high electric charges were detected on a short timescale, and in some cases a proportionality of signal strength and intensity of the respective process was reported. The potency of brittle-type fragmentation of molten volcanic rock to generate significant electrical signals on a short timescale in laboratory experiments was reported by Biittner et al [1997].…”
Section: Copyright 2000 By the American Geophysical Unionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermohydraulic explosion represents the most violent phreatomagmatic activity, that is, the phreatomagmatic explosion [Zimanowski, 1998]. In the context of fragmentation of solid material [e.g., Petrenko and Gluschenkov, 1996;Yoshida et al, 1997Yoshida et al, , 1998], impact events [e.g., Crawford and Schultz, 1988; Adushkin and Soloviev, 2819 1996], and nuclear explosion [e.g., Zablocki, 1966], very high electric charges were detected on a short timescale, and in some cases a proportionality of signal strength and intensity of the respective process was reported. The potency of brittle-type fragmentation of molten volcanic rock to generate significant electrical signals on a short timescale in laboratory experiments was reported by Biittner et al [1997].…”
Section: Copyright 2000 By the American Geophysical Unionmentioning
confidence: 99%
“…Experimental studies using very low viscosity ion and metal melts have shown that during explosive molten fuelcoolant interaction (thermohydraulic explosion) brittle fragmentation of the melt plays the key role for explosive surface enlargement and energy conversion [Zimanowski et al, 1997b; Bgttner and Zimanowski, 1998]. Thermohydraulic explosion represents the most violent phreatomagmatic activity, that is, the phreatomagmatic explosion [Zimanowski, 1998] 1996], and nuclear explosion [e.g., Zablocki, 1966], very high electric charges were detected on a short timescale, and in some cases a proportionality of signal strength and intensity of the respective process was reported. The potency of brittle-type fragmentation of molten volcanic rock to generate significant electrical signals on a short timescale in laboratory experiments was reported by Biittner et al [1997].…”
Section: Introductionmentioning
confidence: 99%
“…The transients were so large in the vicinity of the shot chamber t.hat quantitative measurement of resistivity changes would have been extremely difficult. The potential, however, was interpreted by Zablocki (1966) and Rivers similar effects were not observed with the small chemical explosives also used in this study. In a different experiment,, an electrical signal generated (Martner and Sparks, 1959) at the instant a seismic wave intersected the base of the weathered layer was observed.…”
Section: Introductionmentioning
confidence: 56%
“…In large underground nuclear tests, lowfrequency electrical transients have been observed at the instant of detonation (Zablocki, 1966). The transients were so large in the vicinity of the shot chamber t.hat quantitative measurement of resistivity changes would have been extremely difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Thus it is natural to associate this signal component with the Compton electron model, as has been suggested by Bomke et al [1964]. Finally, Zablocki [1966] has reported measurements in the micropulsation to lower ELF range at a relatively short distance (15.7 km) from two low-altitude detonations of the 1958 Hardtack test series in Nevada. The polarization of the signals observed in these measurements implies a nearly vertical electric dipole source, as would be expected from the Compton electron model of signal generation as a result of the earth-atmosphere interface or of the atmospheric density gradient, rather than the magnetic dipole source that would result from the field displacement model.…”
Section: Experimental Results and Their Interpretationmentioning
confidence: 77%